Dispositional and induced optimism lead to attentional preference for faces displaying positive emotions: An eye-tracker study. Issue 3 (3rd May 2016) - Peters, Madelon L.; Vieler, Julia S.E.; Lautenbacher, Stefan
Abstract : The aim of this study was to examine whether dispositional optimism and induced optimism are associated with an attentional bias for positive stimuli. Fifty-six healthy participants performed an eye-tracking task twice, while their gazing time at faces displaying joy, anger, pain, or a neutral expression was measured. Participants scoring high on dispositional optimism tended to gaze longer at joy faces during the first face-presentation trial compared to participants scoring lower on optimism, and this correlation became significant during the second face-presentation trial. In between the two presentations, participants received either an optimism manipulation or a control manipulation. There was no effect of type of manipulation on gazing behavior but post hoc analyses demonstrated that participants showing an increase in state optimism displayed a significant decrease in gaze duration for anger faces and a nearly significant increase in gaze duration for joy faces.